Cutaneous Hyalohyphomycosis caused by Geotrichum candidum in a Red-Eared Slider Turtle (Trachemys scripta elegans) - Andréia Spanamberg; Mauro Luís da Silva Machado; Carin Elisabete Appelt; Fabio dos Santos Teixeira; Beatriz Fuentes; David Driemeier; Laerte Ferreiro (Acta Scientiae Veterinariae, 2024)
Background: Mycoses in Chelonians have different features; they can be affected by fungi causing shell, tegumental, and/or systemic disease, which can be considered as conventional agents. Geotrichum species are colonies similar to yeast, producing arthroconidia without blastoconidia. The diseases of the shell are one important disorder that might affect the survival of chelonians. They are more often found in aquatic species kept in captivity and are usually caused by poor environmental conditions. Also, bites and accidents that hurt the shell are factors that allow pathogenic organisms, such as bacteria, fungi, or even algae, to colonize and penetrate the shell. This can lead to conditions called septicemic cutaneous ulcerative disease, which causes deep ulcerations This report describes a case of cutaneous hyalohyphomycosis caused by Geotrichum candidum in a turtle. Case: A 3-year-old female Red-Eared Slider Turtle weighing 0.3 kg attacked by a dog 2 weeks earlier and presenting many deeps wounds with necrotic areas in the carapace as the one relevant clinical feature, was assisted at the Service of Dermatology, Hospital de Clínicas Veterinárias, UFRGS, Porto Alegre, Brazil. Samples were obtained from the shell scrapings and the wounded necrotic areas of shell tissues were removed for routine microbiological and histological diagnosis. Direct microscopic examination with mount in 10% KOH revealed the presence septate hyaline hyphae. Bacteriological cultures done on Blood agar and yielded few colonies of Citrobacter freundii. For mycological diagnosis, the material was inoculated onto Sabourad’s Dextrose Agar supplemented with chloramphenicol and Mycosel Agar. Smooth, one-celled, subglobose to cylindrical arthroconidia quite variable in size, consistent with description of Geotrichum candidum. Histology findings of biopsied material stained with Hematoxylin and Eosin (HE) and Periodic Acid-Schiff (PAS), revealed the presence of numerous hyaline septate hyphae among necrotic tissues. Immediately after the clinical examination, in view of the extensive injuries, a subcutaneous single dose of 10,000 UI of benzathine penicillin G, a long therm-acting antibiotic, was administered and a daily topical application of 10% iodine was recommended. Supportive therapy was not necessary due to the animal general good health. The turtle was reexamined only 45 days later showing a little improvement of the lesions and new collected material yielded no bacteria but only pure colonies of G. candidum and still the presence of hyaline septate hyphae on the histopathologic assessment. Then, a treatment with topical nystatin was prescribed and 6 months later, the success of the therapy, was confirmed by the complete resolution of the wounds and the negative results of the third fungal and histological evaluations. Discussion: Geotrichosis has already been reported in animals, including lizards and snakes and reports about Geotrichum species as etiological agents among chelonians have been increasing in recent years. Although the conditions that enable opportunistic infections are similar for all saprobic fungi, clinical cases by Geotrichum species are rare in hosts. We believe that misreporting or misdiagnosis with other species, like Candida, could be the reason it is rarely reported. In this report, and in the other reviewed cases of animal geotrichosis, no predisposing factors are mentioned and the bite probably caused the wound in the shell and allowed the growth of the pathogenic fungus. The appropriate medium and the cultivation of Geotrichum candidum, as well as the use of molecular analysis, can contribute to the successful isolation of these species and make a correct final diagnosis Keywords: geotrichosis, Geotrichum sp., turtle, Chelonians, emerging mycoses, shell mycoses.